Death by `techtonic’ fault - Abd Razak, Dzulkifli (2010)
THE world is about to witness a "techtonic" shift induced by the iPad. It is expected to result in a new, qualitatively different experience compared with a conventional personal computer. For starters, it is packed with much more sophisticated functionality for fingertip interface. It is light, easy to operate and portable. It is no more than a tablet with a relatively large screen. Some liken it to a NokiaKindleNintendo machine interconnecting seamlessly. It is a communication gadgetcumreaderandgame device rolled into one — available simultaneously at multitouch.